Racial Differences in Diuretic Efficiency, Plasma Renin, and Rehospitalization in Subjects With Acute Heart Failure - Morris, Alanna A.; Nayak, Aditi; Ko, Yi-An; D’Souza, Melroy; Felker, G. Michael; Redfield, Margaret M.; Tang, W.H. Wilson; Testani, Jeffrey M.; Butler, Javed (Circulation. Heart failure, 2020)
Black patients have higher rates of hospitalization for acute heart failure than other race/ethnic groups. We sought to determine whether diuretic efficiency is associated with racial differences in risk for rehospitalization after acute heart failure.BACKGROUNDBlack patients have higher rates of hospitalization for acute heart failure than other race/ethnic groups. We sought to determine whether diuretic efficiency is associated with racial differences in risk for rehospitalization after acute heart failure.A post hoc analysis was performed on 721 subjects (age, 68±13 years; 22% black) enrolled in 3 acute heart failure clinical trials: ROSE-AHF (Renal Optimization Strategies Evaluation in Acute Heart Failure), DOSE-AHF (Diuretic Optimization Strategy Evaluation in Acute Decompensated Heart Failure), and CARRESS-HF (Cardiorenal Rescue Study in Acute Decompensated Heart Failure). Repeated-measures ANOVA was used to test for a race×time effect on measures of decongestion. Diuretic efficiency was calculated as net fluid balance per total furosemide equivalents. In a subset of subjects, Cox regression was used to examine the association between race and rehospitalization according to plasma renin activity (PRA).METHODSA post hoc analysis was performed on 721 subjects (age, 68±13 years; 22% black) enrolled in 3 acute heart failure clinical trials: ROSE-AHF (Renal Optimization Strategies Evaluation in Acute Heart Failure), DOSE-AHF (Diuretic Optimization Strategy Evaluation in Acute Decompensated Heart Failure), and CARRESS-HF (Cardiorenal Rescue Study in Acute Decompensated Heart Failure). Repeated-measures ANOVA was used to test for a race×time effect on measures of decongestion. Diuretic efficiency was calculated as net fluid balance per total furosemide equivalents. In a subset of subjects, Cox regression was used to examine the association between race and rehospitalization according to plasma renin activity (PRA).Compared with nonblack patients, black patients were younger and more likely to have nonischemic heart failure. During the first 72 to 96 hours, there was greater fluid loss (P=0.001), decrease in NT-proBNP (N-terminal pro-B-type natriuretic peptide; P=0.002), and lower levels of PRA (P<0.0001) in black patients. Diuretic efficiency was higher in black than in nonblack patients (403 [interquartile range, 221-795] versus 325 [interquartile range, 154-698]; P=0.014). However, adjustment for baseline PRA attenuated the association between black race and diuretic efficiency. Over a median follow-up of 68 (interquartile range, 56-177) days, there was an increased risk of all-cause and heart failure-specific rehospitalization in nonblack patients with increasing levels of PRA, while the risk of rehospitalization was relatively constant across levels of PRA in black patients.RESULTSCompared with nonblack patients, black patients were younger and more likely to have nonischemic heart failure. During the first 72 to 96 hours, there was greater fluid loss (P=0.001), decrease in NT-proBNP (N-terminal pro-B-type natriuretic peptide; P=0.002), and lower levels of PRA (P<0.0001) in black patients. Diuretic efficiency was higher in black than in nonblack patients (403 [interquartile range, 221-795] versus 325 [interquartile range, 154-698]; P=0.014). However, adjustment for baseline PRA attenuated the association between black race and diuretic efficiency. Over a median follow-up of 68 (interquartile range, 56-177) days, there was an increased risk of all-cause and heart failure-specific rehospitalization in nonblack patients with increasing levels of PRA, while the risk of rehospitalization was relatively constant across levels of PRA in black patients.Higher diuretic efficiency in black patients with acute heart failure may be related to racial differences in activity of the renin-angiotensin-aldosterone system.CONCLUSIONSHigher diuretic efficiency in black patients with acute heart failure may be related to racial differences in activity of the renin-angiotensin-aldosterone system.